PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN Siklus Belajar 5E (Learning Cycle 5E) PADA KONSEP SISTEM EKSKRESI - Shanti, Nenen; Ukit, Ukit (Jurnal BIOEDUIN, 2018)
The purpose of this research is to know the improvement of motivation and learning outcome of the students of Cross-Interest Class (IIS-1, IIS-2, and IIS-3) in Biology lesson of Basic Competence of Excretory System using Learning Cycle 5E Model in MAN 2 Bandung. The method used in this research was classroom action research (PTK). Each cycle was done in 2 times meeting. Data collection techniques used ware observation and tests. The data analysis technique takes the description of teacher and student learning activities during the action using learning cycle 5E model, then calculated the number and average, and for the learning outcome was calculated by the total number of complete and unfinished students and the percentage. From the results obtained that the use of learning cycle 5E model can improve the motivation of learning class of Cross-Interests (IIS-1, IIS-2, and IIS-3) in Biology lessons of basic competence of Excretory System in MAN 2 Bandung. It was evidenced by the increase of student learning motivation after action (cycle I and cycle II). The high learning motivation was accompanied by the increase of students' learning outcomes after the action where the average score of 81.61, 42 students (95.45%) and the student learning outcome before the cycle was on average of 70.58 with 13 students (34.21%), 1st cycle average learning outcomes was 77.45 with 30 students (78.95%) and increased in the second cycle with an average of 85.34 with 35 students (92.11%)